1996
DOI: 10.1046/j.1365-2249.1996.d01-865.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antigenic determinants of the Leishmania infantum histone H3 recognized by antibodies elicited during canine visceral leishmaniasis

Abstract: SUMMARYIn the present study we show that sera from dogs naturally infected with the protozoan parasite Leishmania infantum contain antibodies that specifically react with the parasite histone H3. Using synthetic peptides covering the complete sequence of the protein we located the linear antigenic determinants within the 40 amino-terminal amino acids of the molecule. In addition to the complete form of the protein (rLiH3), two regions of the Leishmania histone H3 were expressed as recombinant proteins: the rLi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…At first glance, histone proteins would not seem to be good vaccine candidates because they are among the most highly conserved proteins and are thought to be targets for the induction of autoimmunity. However, the sequences of our cDNAs (data not shown) and published reports (21,26,27) indicate that there is a very low level of homology between the Leishmania histone proteins and the mammalian homologues. Several of the Leishmania histone proteins have been demonstrated to be targets of the humoral immune response in canine VL (26,27).…”
Section: Vol 68 2000 Vaccine Candidates For Visceral Leishmaniasis mentioning
confidence: 60%
See 1 more Smart Citation
“…At first glance, histone proteins would not seem to be good vaccine candidates because they are among the most highly conserved proteins and are thought to be targets for the induction of autoimmunity. However, the sequences of our cDNAs (data not shown) and published reports (21,26,27) indicate that there is a very low level of homology between the Leishmania histone proteins and the mammalian homologues. Several of the Leishmania histone proteins have been demonstrated to be targets of the humoral immune response in canine VL (26,27).…”
Section: Vol 68 2000 Vaccine Candidates For Visceral Leishmaniasis mentioning
confidence: 60%
“…However, the sequences of our cDNAs (data not shown) and published reports (21,26,27) indicate that there is a very low level of homology between the Leishmania histone proteins and the mammalian homologues. Several of the Leishmania histone proteins have been demonstrated to be targets of the humoral immune response in canine VL (26,27). This seroreactivity was specific to the Leishmania histones, with no cross-reactivity to the mammalian histone homologs.…”
Section: Vol 68 2000 Vaccine Candidates For Visceral Leishmaniasis mentioning
confidence: 60%
“…Similar responses against histone H3, histone H2B, and a fragment of histone H4 from L. infantum were described thereafter (17,18). The investigators mapped the linear epitopes of histones using synthetic peptides.…”
mentioning
confidence: 77%
“…Previous work has shown that all the core histones from L. infantum induce a significant humoral response during CVL (16,17,18). Among them, histones H3 and H2A are recognized the most (81 and 78%, respectively) by sera from dogs with visceral leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…The term 'conserved proteins' has been traditionally applied to a series of protein families that show remarkable evolutionarily conservation, and are generally essential for the preservation of the cellular function. (Soto et al, 1996;Soto et al, 1999), and also against L. braziliensis histone H1 . The researchers mapped the linear epitopes of histones using synthetic peptides, and their findings led to the conclusion that the humoral immune response against the Leishmania histones was triggered by the less conserved regions of the molecule (reviewed in Requena et al, 2000;Carmelo et al, 2002).…”
mentioning
confidence: 94%